2020
DOI: 10.1101/2020.02.11.941120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tough Hydrogel-Based Biocontainment of Engineered Organisms for Continuous, Self-Powered Sensing and Computation

Abstract: Genetically modified microorganisms (GMMs) can enable a wide range of important applications, including environmental sensing, precision therapeutics, and responsive materials. However, containment of GMMs to prevent environmental escape and satisfy regulatory requirements is a bottleneck for real-world use 1-7 . While biochemical strategies have been developed to restrict unwanted growth and replication of GMMs in the environment 8-12 , there is a need for deployable physical containment technologies to achie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…This suggested that cells secreted fluorescent proteins while being encapsulated within the SA hydrogel beads. This phenomenon was also observed in other studies [14,27]. Nevertheless, we cannot deny a possibility that the cells may have escaped from the hydrogel beads and produced fluorescent proteins while growing in medium.…”
Section: Experimental Analysissupporting
confidence: 85%
“…This suggested that cells secreted fluorescent proteins while being encapsulated within the SA hydrogel beads. This phenomenon was also observed in other studies [14,27]. Nevertheless, we cannot deny a possibility that the cells may have escaped from the hydrogel beads and produced fluorescent proteins while growing in medium.…”
Section: Experimental Analysissupporting
confidence: 85%
“…Detection of physiologically relevant molecules, that are usually weak in nature, with stimuli-responsive ELMs has been achieved with biological paper analytical devices (bioPADs), 168,169 tough hydrogel biocontainment platforms, 170 and a wireless analytical device. 171 bioPADs composed of filter paper, ink, genetically engineered yeast, and hydrogel have been designed to detect doxycycline at concentrations down to 0.3 mg mL À1 .…”
Section: Biosensing Technologies For Molecule Detection and Diagnosticsmentioning
confidence: 99%
“…The tough biocontainment ELMs were capable of sensing heme released from defibrinated blood and producing a significant increase in bioluminescence activity. 170 A monitoring device suitable for in vivo sensing of gastrointestinal molecules has been previously demonstrated by incorporating the above-mentioned heme responsive bacterial strain in a wireless readout capsule. The ingestible micro-bioelectronic device (IMBED) combines bacteria with microelectronics to enable local sensing of disease-related biomolecules (heme, AHL, thiosulfate) associated with the state of disease in the gastrointestinal tract.…”
Section: Biosensing Technologies For Molecule Detection and Diagnosticsmentioning
confidence: 99%
“…One limitation is the exposure of the genetically engineered E. coli to the environment, which precludes this technology from implementation in open environmental settings. Various biocontainment strategies have been developed to circumvent this issue, including genetic safeguards, such as engineered auxotrophy ( 52 ), and physical containment ( 53 ). Alternatively, one could sterilize the capsules after production of the relevant functional protein.…”
Section: Discussionmentioning
confidence: 99%